2018
DOI: 10.4066/biomedicalresearch.40-18-526
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and its gastrointestinal problems: A review

Abstract: Metformin is a biguanide class of drugs and has been recommended as first-line therapy for type 2 diabetes. It has a good safety profile, efficacy, comparatively reduced cost, and potential cardiovascular benefits. Metformin is an insulin-sensitizing agent, its bioavailability is 50%-60%. Generally, A1C levels are lowered by 1.5% points by metformin monotherapy. Treatment with metformin decreases fasting plasma glucose concentrations by 25% to 30% and decreases the production of glucose. Metformin reduces hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
1
19
0
2
Order By: Relevance
“…In this study, we found that metformin use emerged as an independent factor for gastroparesis symptoms in patients with T2DM. However, since The most common gastrointestinal side effects of metformin are diarrhea, nausea, abdominal pain and heartburn which were not frequently encountered in the present study, this might eliminate the possibility of metformin as a cause of GI symptoms in the current study [6465]. Similar findings were observed by Dickman R. et al [34] regarding metformin use and the risk of gastroparesis symptoms (OR = 1.97, 95% CI = 1.19–3.28, p < 0.05), and they related this relationship to the possibility of a synergistic effect of metformin with gastroparesis to produce more GI symptoms, or the possibility that the presence of post-prandial distress syndrome was a cause of GI symptoms, rather than delayed gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that metformin use emerged as an independent factor for gastroparesis symptoms in patients with T2DM. However, since The most common gastrointestinal side effects of metformin are diarrhea, nausea, abdominal pain and heartburn which were not frequently encountered in the present study, this might eliminate the possibility of metformin as a cause of GI symptoms in the current study [6465]. Similar findings were observed by Dickman R. et al [34] regarding metformin use and the risk of gastroparesis symptoms (OR = 1.97, 95% CI = 1.19–3.28, p < 0.05), and they related this relationship to the possibility of a synergistic effect of metformin with gastroparesis to produce more GI symptoms, or the possibility that the presence of post-prandial distress syndrome was a cause of GI symptoms, rather than delayed gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…They are most likely related to high concentration of metformin in the intestine, increased secretion of serotonin from enterochromaffin cells, decreased ileum absorption of the bile acids, increased secretion of GLP-1 from enterocytes and altered microbiome. All these factors have a substantial influence on gastrointestinal regulation, particularly intestinal motility and secretion [ 294 ].…”
Section: Safety Of Metforminmentioning
confidence: 99%
“…These findings are of clinical importance because in the younger population vitamin B12 is often associated with gastroparesis, megaloblastic anemia and coeliac disease. At least three putative mechanisms of metformin-induced deficiency of vitamin B12 have been proposed, including: (1) alteration of microbiome resulting in the binding of the intrinsic factor-vitamin B12 complex (IF-vitamin B12 complex) to bacteria and blocking its absorption into circulation, (2) altering the intestinal motility and (3) inhibition of the calcium-dependent IF-vitamin B12 complex binding to the receptor located in the terminal ileum [ 294 ]. The risk of lactic acidosis is described in the section titled “Nephroprotection”.…”
Section: Safety Of Metforminmentioning
confidence: 99%
“…penggunaan insulin dapat mengontrol glukosa darah dengan baik, namun beberapa pasien mengalami efek negatif dari penggunaan insulin yaitu merasa takut, sakit, cemas dan tidak nyaman karena efek samping yang ditimbulkan yaitu hipoglikemia 9 . Selain insulin, terdapat beberapa efek samping antidiabetik oral yang kerap muncul misalnya metformin dapat menyebabkan gangguan gastrointestinal seperti mual, muntah, diare serta asidosis laktat sebesar 20-30% 10 . Akarbose dapat menyebabkan perut kembung dan diare 11 .…”
Section: Meskipununclassified